Kepastian Hukum Ketentuan Pelaku Utama Dalam Kriteria Justice Collaborator di Indonesia - Amelia Elisabeth Putri Kusuma; Ade Adhari (Indonesian Journal of Criminal Law, 2021)
The purpose of this research is to analyze and understand the application of main suspect of justice collaborator criteria in Indonesia. This research is a normative law research, namely law research conducted by examining legal books, legal journals and other library materials as well as the secondary data related to justice collaborator. The result of this research is the legal certainty regarding the main suspect of the justice collaborator criteria that has not been fulfilled by the Indonesian Law, so it has the potential to harm the law enforcement process. This is due to lack of understanding of the main suspect of justice collaborator among the law enforcers. Therefore, the intervention of the authorities to improve the current legal system is required in order to achieve the legal objectives. Specifically, justice, expediency, and legal certainty especially regarding the justice collaborator. The Government needs to accommodate this policy in a clear, vivid, and complete rules. Starting from the criteria and the condition, implementation of procedures, the reward, and the protection for the justice collaborator himself.